Community immersion project to enhance medical students understanding of the health needs of the most vulnerable in the community. Issue 1 (25th March 2021) - Rawther, Fathima; Bondje, Sophie; Rahman, Anisah; Duku, Adelaide; Gooneratne, Selani; Beck, Matthew; Ubhi, Surajdeep; Gleeson, Christina; Kumaravel, Bharathy; Harris, Joanne
Abstract : AIM: A group of eight fourth year medical students formed the 'UBMS public health crew' to conduct a community immersion project within elderly ethnic minority communities. The aim of the study was to understand their health perceptions regarding influenza vaccinations and learn about the enablers and barriers in accessing the vaccination. METHODOLOGY: Interviews were held by the students at community lunch clubs with the help of questionnaires. RESULTS: 76 people participated in the focus groups of which 56.5% were Asians and 43% were Irish. Feedback was sought from the students in the form of an online survey. CONCLUSION: This project helped the medical students improve their public health knowledge, gave them an opportunity to interact with members of the community and learn about the health and social problems faced by underserved/vulnerable communities. The students were also able to appreciate the cultural, sociodemographic and psychological determinants of health in an underserved community. Providing such community immersion projects can enable future doctors to be better prepared for care closer to the community and have better insight into patient-centred care. RESULTS: 76 people participated in the focus groups of which 56.5% were Asians and 43% were Irish. Feedback was sought from the students in the form of an online survey. this project helped the medical students improve their public health knowledge, gave them an opportunity to interact with members of the community and learn about the health and social problems faced by underserved/vulnerable communities. The students were also able to appreciate the cultural, sociodemographic and psychological determinants of health in an underserved community. Providing such community immersion projects can enable future doctors to be better prepared for care closer to the community and have better insight into patient-centred care. METHODS: Interviews were held by the students at community lunch clubs with the help of questionnaires. 76 people participated in the focus groups of which 56.5% were Asians and 43% were Irish. Feedback was sought from the students in the form of an online survey which found that this project helped the medical students improve their public health knowledge, gave them an opportunity to interact with members of the community and learn about the health and social problems faced by underserved/vulnerable communities. The students were also able to appreciate the cultural, sociodemographic and psychological determinants of health in an underserved community. Providing such community immersion projects can enable future doctors to be better prepared for care closer to the community and have better insight into patient-centred care. AIM: A group of eight fourth year medical students formed the 'UBMS public health crew' to conduct a community immersion project within elderly ethnic minority communities. The aim of the study was to understand their health perceptions regarding influenza vaccinations and learn about the enablers and barriers in accessing the vaccination. Interviews were held by the students at community lunch clubs with the help of questionnaires. 76 people participated in the focus groups of which 56.5% were Asians and 43% were Irish. Feedback was sought from the students in the form of an online survey which found that this project helped the medical students improve their public health knowledge, gave them an opportunity to interact with members of the community and learn about the health and social problems faced by underserved/vulnerable communities. The students were also able to appreciate the cultural, sociodemographic and psychological determinants of health in an underserved community. Providing such community immersion projects can enable future doctors to be better prepared for care closer to the community and have better insight into patient-centred care.